Pengaruh Bahasa Jawa Cilacap dan Bahasa Sunda Brebes Terhadap Pencilan Bahasa (Enklave) Sunda di Desa Madura Kecamatan Wanareja Kabupaten Cilacap - Hetty Catur Ellyawati (Jurnal CULTURE (Culture, Language, and Literature Review), 2015)
Enclave is the use of vocabularies that is different from the surrounding villages. The differences can be obtained by the influences of the other vocabularies from the nearest villages. The influences can be in morphological form, phonological or in lexical form. The aim of this research is to show that there are some influences in morphological, phonological and lexical forms in Sundanese language in Madura Village, Wanareja District from Javanese language in Cilacap and Sundanese language in Brebes. This research is library research because to collect the data, the writer used documents. To analyse the data, it is used Padan and Agih Method. The result of this research is that there are some influences happened in Sundanese Language in Cilacap village. The influence in lexicon is from the historical background of the village, while in phonetic, some sound changes are in assimilation, metathesis and anatixis processes. In morphology, the influent process is in reduplication, that are, reduplication and affixation. Thus, the conclusion of this research is Sundanese language in Madura Village, Wanareja District is influenced by languages nearest to the village.  Keywords: enclave, reduplication, morphological form, phonological form, lexical form